NILAI DAN PENGARUHNYA TERHADAP PERENCANAAN KEUANGAN KELUARGA DALAM PEMBELIAN ASURANSI JIWA - Finira, Denissa Chika; Yuliati, Lilik Noor (Jurnal Ilmu Keluarga dan Konsumen, 2013)
Life insurance is one of many ways to anticipate risks in the future. The aim of this research was to analyzevalue due to the priorities scale of its dimension, to analyze information access, and to analyze their influencestowards financial planning in purchasing life insurance in Kebon Pedes Area, Tanah Sareal Subdistrict, BogorCity, West Java Province. The location had prosperous family I, II, and III plus, the most in Tanah SarealSubdistrict. The samples of this research was 84 families that was selected by simple random sampling. Data wasanalyzed by multiple linear regression. The result of this research showed that the respondents gettinginformation was 90,5 percent of the sample and the rest did not. Maximum number of that accepted sources therespondents by were 9 sources. The trusted one was life insurance agent. Moreever, friends/neighbours andfamily were also trusted by each 16,7 and 6,0 percent of the respondent. The dimension of the value havinghighest priority was universalism which was one of the social values. Value was significantly affecting financialplanning on life insurance purchasing.